Lecture Transcripts for Frequency and Framing Keywords in EMI - Siegel, Joseph (Stockholm University, 2025)
English medium instruction (EMI) courses can present challenges for both lecturers and students. The lecturer’s planning and delivery of lecture content, especially in terms of spoken output, has rarely been investigated. This study focused on an analysis of two university lectures from different disciplines. In pre-lecture discussions with the researcher, lecturers had indicated a set of key concepts and important words that they expected the students to recognize and learn more about during the lectures. Based on those lists, the lecture transcripts were scrutinized in terms of keyword frequency as well as in relation to Sinclair and Coulthard’s (1975) framework for understanding classroom discourse and speaker output, which allowed patterns of keyword use within lecture discourse to be identified. Comparative results from the analysis showed keywords being more frequent in the Sociology lecture than in the Robotics class. In terms of patterns of lecturer output, the majority of keywords were included in the categories “Informative” and “Comment”; however, quantitative and proportional differences in these patterns were also observed. Practical advice for EMI lecturers in relation to keyword frequency and framing is offered to account for language proficiency levels of teachers and/or students in similar higher education contexts. The data set underpinning the article consists of two lecture transcripts, one from sociology and one from robotics.
Keywords: LOTE, ESL and TESOL curriculum and pedagogy; Educational Sciences; Utbildningsvetenskap